Influence of Social Cognitive Cooperation Model with Techniques of Cognitive Restructuring and Engineering Modeling on Self Abasement Students - Diastuti, Ni Putu Nia; Arum MWP, Dewi; Dharsana, I Ketut (Department of Guidance and Counseling, FIP, Undiksha, 2017)
This research is a quasi research (